New Fixed Point Results in F-Quasi-Metric Spaces and an Application. (18th June 2020) - Ghasab, Ehsan Lotfali; Majani, Hamid; Karapinar, Erdal; Rad, Ghasem Soleimani
Abstract : The main goal of the present paper is to obtain several fixed point theorems in the framework of F -quasi-metric spaces, which is an extension of F -metric spaces. Also, a Hausdorff δ -distance in these spaces is introduced, and a coincidence point theorem regarding this distance is proved. We also present some examples for the validity of the given results and consider an application to the Volterra-type integral equation.